Resolution of long-lasting laryngeal manifestations using glucocorticoids and tumor necrosis factor-α inhibitor therapy in a patient with mouth and genital ulcers with inflamed cartilage syndrome - Tomohiro Suzuki; Toshihiko Komai; Misaki Koyama; Kento Koda; Rumi Ueha; Hirofumi Shoda; Keishi Fujio (Journal of Rheumatic Diseases, 2025)
Mouth and genital ulcers with inflamed cartilage (MAGIC) syndrome is a rare disorder characterized by features of both relapsing polychondritis (RP) and Behçet's disease (BD), with multi-organ involvement, including inflammation and destruction of cartilaginous tissues. This report describes a patient with MAGIC syndrome who responded to immunosuppressive therapy for long-lasting laryngeal inflammation and provides the first description of a patient with MAGIC syndrome positive for human leukocyte antigen (HLA)-A26. Here we present a 49-year-old male with recurrent oral and genital ulcers, hoarseness, and swallowing difficulties. Laryngoscopy showed bilateral vocal fold immobility, and contrast-enhanced magnetic resonance imaging (MRI) demonstrated inflammation in the cricoid, arytenoid, and auricular cartilages. The patient was diagnosed with MAGIC syndrome based on the presence of both RP and BD criteria. Treatment with high-dose corticosteroids and adalimumab biosimilar resulted in significant improvement in hoarseness and MRI findings of cartilage inflammation. This case highlights the effective use of immunosuppressive therapy for managing long-lasting laryngeal involvement in MAGIC syndrome, potentially avoiding the need for invasive interventions such as tracheostomy.